Peranan Dinas Tenaga Kerja dan Transmigrasi dalam Memberi Perlindungan Hukum Terhadap Pekerja Sistem Kontrak - Prasetya, Yogie Agung (Fakultas Hukum Universitas Kanjuruhan Malang, 2014)
Good government in the field of employment as though less of attention to the fate of the workers. This is supported by the doctrine of stability which is weakened the bargaining position of employment. Especially with the many companies that use contract system (outsourcing)Â that makes the most workers feel their rights are lacking. the lack of government and the rules of employmentÂ became occurrence of contract systems practice (outsourcing) and more contract in Indonesia.Based on the fact that occur in the field, so the writer make the statement of problems: the problem that is faced by the official of employment in Mojokerto regency in given the law protection for outsourcing employment, the efforts of official employment in Mojokerto regency in given the law protection for outsourcing employment. The purposes of this research are to describe and to analyze the problem which are faced and the role done by the official of employment in Mojokerto regency in given the law protection for outsourcing employment.To answer the statement of problem and research purposes are used sociological research methods. the type of data include primary data and secondary data was done by doing research in the field and completed by research in the library. While to get a sample that is by doing interview with the parties who are be investigated.From the results and discussion there are many violations for contract system of employment (outsourcing) which the rights are not given by the company. the lack of supervision in the field of employment by employee in official of employment and transmigration in Mojokerto regency. many ofÂ unemployments and the minimum of job vacancy is marked with the many of cases included of official employment in Mojokerto regency. Therefore, it needs the support of all parties, especially the government to be more selective to give protect to employment and give the firm sanctions for employers who violate the employment laws.